Metodološke dileme in njihove rešitve v raziskovalnem načrtu z zaporedno uporabo kvantitativnih in kvalitativnih metod - Hlebec, Valentina (Teorija in praksa, 2012)
This paper evaluates the explanatory research design with participant selection in mixed methods studies with regard to the components of the research design, such as time, cost, access to the data, the sampling techniques used, the selection of participants, the quality of indicators and data quality. The selected design and methodological dilemmas that occur while implementing this research design using secondary quantitative data are first presented in the case of our own research. Next, a meta-analysis of selected articles critically evaluates methodological dilemmas when it comes to explanatory design with participant selection in mixed methods studies. Even though there are certain restrictions with the application of secondary quantitative data, we still encourage their use because the benefits of using secondary data outweigh the identified weaknesses. However, when using secondary data in explanatory research design with participant selection in mixed methods studies researchers should still critically evaluate the main limitations and discuss the validity of the solution that is chosen.
Keywords: Družboslovna metodologija; Social science methodology; Quantitative method; Kvantitativna metoda; Kvalitativna metoda; Qualitative method; raziskovalna dejavnost; načrti